Effect of psychological interventions on outcomes for caregivers of hematopoietic stem cell transplant patients: Protocol for a systematic review and planned meta-analysis. - Ranjita Poudel; Min-Jeong Yang; Skye O Dougan; Helen Yates; Bradley Brown; Sierra Washington; Aarya P Satardekar; Mary Katherine Haver; Christine Vinci (PLoS ONE)
Caregivers of Hematopoietic Stem Cell Transplant (HSCT) recipients bear significant responsibilities involving commitment to be available 24/7, up to at least 100 days post-transplant or longer, and to provide emotional and physical support to the recipient. This extended caregiving, along with managing all other household responsibilities, can result in an increased caregiver burden, which is associated with reduced quality of life (QoL) and compromised psychological, and physical well-being. In recent years, there has been increased attention to interventions addressing the mental health outcomes of caregivers of HSCT patients. However, there remains a limited understanding of the feasibility and effectiveness of existing interventions targeted to this population. This review aims to systematically evaluate existing psychological interventions for caregivers of HSCT patients and report on: 1) the feasibility and acceptability of these interventions, and 2) the efficacy of these interventions on caregivers' psychological outcomes. A systematic literature search for studies evaluating psychological interventions targeted to caregivers of HSCT patients was conducted in English through the following databases: Ovid MEDLINE (Wolters Kluwer), Embase (Elsevier), CINAHL Complete (EBSCO), APA PsycArticles (EBSCO), APA PsycInfo (EBSCO). Two reviewers will independently identify the studies, extract relevant data, and conduct quality and risk of bias assessments. Discrepancies in coding will be discussed between the two reviewers, and a third reviewer will resolve pending disagreements. Within the systematic review, all eligible studies will be summarized descriptively. If data allows, we will further utilize meta-analysis to quantitatively evaluate the efficacy of these psychological interventions tested in RCTs. The association between intervention type, modality, duration, and efficacy will be assessed via subgroup analysis. Ethics approval is not required as this study will only include secondary data from already published studies. The outcomes will be shared through scientific conferences and peer-reviewed publications. This protocol is registered in PROSPERO: CRD42024489695.